Continuing need for close US-European ties - Latter, Richard (HMSO LondonGB, 1994)
Looks at US domestic concerns such as the economy, declining social cohesion, the changing ethnic balance and implications for foreign policy. Focuses on European concerns viz. the European economy and trade; rebuilding Eastern Europe and ethnic wars. Discusses maintaining close US-European relations in areas such as peacekeeping; NATO; and the European Union.